Does Grazing Cover Crops Impact Soil Properties? - A. K. Obour; L. M. Simon; J. D. Holman; S. K. Johnson (Kansas Agricultural Experiment Station Research Reports, 2021)
Grazing of cover crops (CCs) by cattle could provide supplemental forage and additional revenue to offset grain yield losses when CCs are grown in semiarid rainfed cropping systems. However, grazing CCs could reduce the amount of residue retained on the soil surface and subsequently affect soil physical and chemical properties. This study evaluated effects of grazing CCs on soil bulk density, aggregate stability, and chemical properties using soil samples collected from three producer fields in west central Kansas that had paired grazed and non-grazed CC treatments, as well as adjacent native perennial pastures. Across sites, CC residue after grazing averaged 2650 lb/a compared to 3741 lb/a for the non-grazed CCs, representing a 29% decrease in CC biomass with grazing. Bulk density, aggregate size distribution, and mean weight diameter (MWD) were not different (P>0.05) between grazed and non-grazed CCs. The MWD under perennial pasture was 0.148 in., approximately 2.9-fold greater than MWD with grazed (0.050 in.) or non-grazed CCs (0.051 in.). Soil pH and soil organic carbon (SOC) did not differ (P>0.05) between the grazed and non-grazed CCs. Soil nitrate (NO3-N), phosphorus (P), iron (Fe), manganese (Mn), and copper (Cu) concentrations with grazed or non-grazed CCs were greater than in pasture. Our findings showed grazing of CCs may be a management option to intensify NT cropping systems with little negative effects on soil bulk density, aggregate stability, or extractable nutrient concentrations.
Keywords: Cover crops; grazing; soil health